BILIARY ATRESIA IS ASSOCIATED WITH POLYSPLENIA AND SITUS INVERSUS ON ULTRASOUND, A CASE REPORT STUDY. - Tukwasibwe, Evalyne; Malumba, Richard; Ankunda, Racheal; Kaakyo, Mary (Student’s Journal of Health Research Africa, 2023)
Biliary atresia is a destructive, idiopathic, and inflammatory cholangiopathy that affects intra and extra-hepatic bile ducts leading to fibrosis and obliteration of the biliary tract and development of liver cirrhosis. The polysplenia syndrome is the most common anomaly, being found among patients with atresia, and is characterized by polysplenia/asplenia associated with a midline liver, interruption of the inferior vena cava, preduodenal portal vein, situs inversus and/or intestinal malrotation. Biliary atresia has an incidence of 1 in 10,000-15,000 live births and is more common in females than males. I report a case of a 5 months old baby boy who presented with yellow eyes since birth and abdominal distension for one week. The diagnosis of Biliary atresia, polysplenia, and situs inversus is usually based on clinical findings. Ultrasonography and Intraoperative cholangiogram are useful tools. The most suitable recommendable treatment for this specific case is surgery. This case study is to fill the knowledge gap among sonographers/radiographers regarding the existence of such cases to guide the management of those conditions, especially among infants.